2002
DOI: 10.1007/bf03344070
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of left ventricular hypertrophy and arrhythmias after lanreotide-induced GH and IGF-I decrease in acromegaly. A prospective multi-center study

Abstract: We report the results of a prospective Italian multi-center study of the effects of lanreotide, a slow-release somatostatin analog, on left ventricular morphology and function and on the prevalence of ventricular arrhythmic events in 19 patients with active, newly diagnosed, uncomplicated acromegaly. Cardiac features were evaluated with Doppler-echocardiography and 24-h Holter ECG monitoring at baseline and after 6 months of lanreotide therapy. Fifteen patients (78.9%) had left ventricular hypertrophy. Lanreot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 31 publications
3
69
3
2
Order By: Relevance
“…As far as geometric cardiac pattern is concerned, cardiac hypertrophy was present in the majority of our untreated patients, as expected (2,10,31). In agreement with several previous studies (10 -12), left ventricular mass significantly decreased after therapy, without a significant correlation with dCVF.…”
Section: Discussionsupporting
confidence: 92%
“…As far as geometric cardiac pattern is concerned, cardiac hypertrophy was present in the majority of our untreated patients, as expected (2,10,31). In agreement with several previous studies (10 -12), left ventricular mass significantly decreased after therapy, without a significant correlation with dCVF.…”
Section: Discussionsupporting
confidence: 92%
“…Almost a half of a small cohort of ACM patients presented complex ventricular arrhythmias (Lown III-IV) in one study, especially those with a long disease duration (Kahaly et al 1992). A multicentric study performed in Italy using 24-h ECG-Holter monitoring reported a lower but still very significant rate of ventricular extrasistoles (in 33% of the ACM cases evaluated; Lombardi et al 2002). Twenty-four-hour ECG-Holter monitoring might be useful in the preoperative evaluation of the patients (Fedrizzi & Czepielewski 2008), especially those with clinically detected abnormalities.…”
Section: Complicationsmentioning
confidence: 97%
“…Cardiovascular system-Both octreotide LAR and lanreotide SR Hradec et al, 1999;Lombardi et al, 2002) reduced left ventricular hypertrophy and improved diastolic dysfunction especially in younger patients with shorter disease duration. Increased exercise capacity, normalization of ejection fraction and suppression of ventricular premature beats were also observed .…”
Section: Symptom Controlmentioning
confidence: 99%